2004
DOI: 10.1021/bi036178q
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Inhibits the Repair of Photosystem II by Suppressing the Translation Elongation of the D1 Protein in Synechocystis sp. PCC 6803

Abstract: Singlet oxygen, generated during photosynthesis, is a strong oxidant that can, potentially, damage various molecules of biological importance. We investigated the effects in vivo of singlet oxygen on the photodamage to photosystem II (PSII) in the cyanobacterium Synechocystis sp. PCC 6803. Increases in intracellular concentrations of singlet oxygen, caused by the presence of photosensitizers, such as rose bengal and ethyl eosin, stimulated the apparent photodamage to PSII. However, actual photodamage to PSII, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
257
5
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(272 citation statements)
references
References 42 publications
6
257
5
4
Order By: Relevance
“…Mutants without zeaxanthin or echinenone and especially the double mutant defective of both zeaxanthin and echinenone are sensitive to photooxidative damage (Schäfer et al, 2005). Salt stress has been suggested to induce ROS production, and both photosynthesis and translation are known to be ROS sensitive (Nishiyama et al, 2004(Nishiyama et al, , 2006Kojima et al, 2007). Enhanced accumulation of carotenoids in salt stress might actually be important for reactivation of photosynthesis and translation during salt acclimation.…”
Section: Sigb Factor Regulates the Carotenoid Content Of The Cellsmentioning
confidence: 99%
“…Mutants without zeaxanthin or echinenone and especially the double mutant defective of both zeaxanthin and echinenone are sensitive to photooxidative damage (Schäfer et al, 2005). Salt stress has been suggested to induce ROS production, and both photosynthesis and translation are known to be ROS sensitive (Nishiyama et al, 2004(Nishiyama et al, , 2006Kojima et al, 2007). Enhanced accumulation of carotenoids in salt stress might actually be important for reactivation of photosynthesis and translation during salt acclimation.…”
Section: Sigb Factor Regulates the Carotenoid Content Of The Cellsmentioning
confidence: 99%
“…3), indicating that the acceleration of photodamage upon the impairment of CEF is attributable to neither the impairment of qE nor the production of hydrogen peroxide. Furthermore, both interruption of the Calvin cycle that causes overreduction of photosynthetic electron transport (Hakala et al, 2005;Murata, 2005, 2006) and the exogenous supply of singlet oxygen (Nishiyama et al, 2004) have been demonstrated to have no effect on the process of photodamage. However, nigericin accelerated photoinhibition in both the presence and absence of chloramphenicol (Fig.…”
Section: Cef Reduces Direct Photodamage To Psiimentioning
confidence: 99%
“…In cyanobacteria, exogenous supply of singlet oxygen and hydrogen peroxide has been demonstrated to inhibit the repair of photodamaged PSII with no effect on the process of photodamage to PSII (Nishiyama et al, 2001(Nishiyama et al, , 2004. This inhibition of the repair occurs through inhibition of the de novo synthesis of PSII proteins, primarily the D1 protein, at the step of translation (Nishiyama et al, 2004Kojima et al, 2007). Inhibition of the synthesis of the D1 protein upon impairment of qE and CEF, therefore, might be attributable to the production of reactive oxygen species (Fig.…”
Section: Cef Reduces Inhibition Of Protein Synthesis-dependent Repairmentioning
confidence: 99%
“…Since the reduction state of Q A linearly increases with irradiance, the probability of photodamage increases under strong light (Melis 1999). While light damages PSII directly, oxidative stress during photosynthesis has been demonstrated to suppress the de novo synthesis of proteins, in particular, the D1 protein, which is required for the repair of PSII (Nishiyama et al 2004. Photodamage or chronic photoinhibition mainly occurs in seaweeds growing in the lower sublittoral zone when exposed to high irradiances (Hanelt 1998).…”
Section: Introductionmentioning
confidence: 99%